2016
DOI: 10.1097/01.aoa.0000489482.52898.30
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Cardiac Evaluation During Uncomplicated Twin Pregnancy With Emphasis on the Diastolic Function

Abstract: (Am J Obstet Gynecol. 2015;213(3):376.e1–e8) Evaluating the cardiac function of pregnant women has shown that when echocardiograms reveal abnormalities there is a heightened risk of obstetric complications such as hypertensive disorders and placental insufficiency. However, most of the studies investigating this association have only focused on singleton gestations and there is a scarcity of literature on how maternal hemodynamics might affect twins. The authors of this paper attempted to address thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…More significant changes have been reported in twin compared to singleton pregnancies, including higher maternal cardiac output (CO) and lower total vascular resistance (TVR) across gestation [2][3][4][5][6][7][8]. In a recent study focusing on maternal haemodynamics in uncomplicated twin gestations, significant changes in systolic and diastolic function were documented from the first to third trimester [9]. Nevertheless, in that study echocardiographic findings were not assessed according to chorionicity due to the small number of monochorionic (MC) gestations included.…”
Section: Introductionmentioning
confidence: 99%
“…More significant changes have been reported in twin compared to singleton pregnancies, including higher maternal cardiac output (CO) and lower total vascular resistance (TVR) across gestation [2][3][4][5][6][7][8]. In a recent study focusing on maternal haemodynamics in uncomplicated twin gestations, significant changes in systolic and diastolic function were documented from the first to third trimester [9]. Nevertheless, in that study echocardiographic findings were not assessed according to chorionicity due to the small number of monochorionic (MC) gestations included.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is evident that even in uncomplicated pregnancies, the maternal cardiovascular system is pushed to its maximum functional limits at the edge of decompensation. This is evident when assessing cardiovascular condition in obese women, advanced maternal age or multiple gestation, where the prevalence and severity of maternal cardiovascular dysfunction at term is significantly increased (Ghi et al 2015;Budderberg et al 2018b). As maternal cardiovascular dysfunction occurs acutely and at the end of pregnancy, late preeclampsia is only infrequently associated with fetal growth restriction -placental dysfunction is short lived and rarely results in fetal growth restriction (Verlohren et al 2014).…”
Section: Pregnancy-induced Cardiovascular Dysfunction Predisposing Tomentioning
confidence: 99%
“…Twin pregnancy differs from singleton pregnancy in many respects like the greater physiological increase in circulating blood volume [1], greater gestational weight gain and newborn weight (sum for twins) [2], shorter pregnancy length [3], persistent systolic dysfunction after delivery [4], and greater risk of peripartum cardiomyopathy in women with twin pregnancies than in those with singleton pregnancies [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In a classical study by Pritchard [1], the mean net increases in circulating blood volume in singleton and twin pregnancies were 1570 mL and 1960 mL, respectively. This causes signi cant differences between singleton and twin pregnancy women in echocardiographic ndings [12][13][14][15][16] and in blood levels of cardiac biomarkers, such as B-type natriuretic peptide (BNP), N-terminal precursor protein BNP fragment (NT-proBNP), and high-sensitivity troponin I (hs-TnI) [17]. Kuleva et al revealed a higher cardiac output in twin than in singleton pregnancies [15], and Ghi et al showed changes in maternal systolic and diastolic function from the rst to the third trimester and a persisting decreased systolic function after delivery [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation